Integrative taxonomy reveals three new species of European Lepidocyrtus lignorum-group (Collembola, Entomobryidae) - Mateos, Eduardo; Álvarez-Presas, Marta (Zootaxa, 2022)
Lepidocyrtus is one of the genera of springtails with the largest number of species in the world. Molecular studies carried out to date on this genus have revealed the existence of a large number of cryptic species. Molecular and morphological studies done with four European populations of the genus have allowed us to describe three new species within the L. lignorum-group: L. fuscocephalus sp. nov., L. milagrosae sp. nov. and L. semicoloratus sp. nov. One of these species is made up of two geographically separate populations that represent two clearly separate but morphologically indistinguishable haplotypes.